Pengaruh Kompetensi, Perilaku Organisasi Dan Komitmen Terhadap Kualitas Laporan Keuangan Direktorat Reserse Narkoba Polda Sumsel - Maulinda Damayanti; Luis Marnisah; Fakhry Zamzam (Program Magister Manajemen Indo Global Mandiri University, 2021)
General purpose financial statements to meet the information needs of all user groups. As such, government financial reports are not designed to meet the specific needs of each user group. However, since the government's financial statements act as a form of accountability in the management of state finances, the report components presented at least include the types of reports and information elements required by statutory provisions (staturory reports). Research Objectives To find out the results of the analysis of the influence of Competence on the quality of financial statements in the Directorate of Drug Investigation of the South Sumatra Police, To find out the results of the analysis of the influence of Organizational Behavior on the quality of financial statements in the Directorate of Drug Investigation of the South Sumatra Police and Also To find out the results of the analysis of the effect of commitment to the quality of financial statements at the Directorate South Sumatra Police Narcotics Detective. The type of data in this study are primary data and secondary data. Primary data is data obtained from first sources, both individuals or individuals, such as interviews or questionnaire results. In this study primary data were taken using a direct questionnaire on primary data sources, namely the National Police and the South Sumatra Police Narcotics Investigation Directorate. While secondary data is data obtained indirectly from the source or is primary data that has been further processed and presented either by the primary data collection party or by other parties in the form of tables and diagrams for further processing. Results and Discussion. The results of statistical calculations are presented in descriptive form to describe the data description by using inferential analysis to find out the relationship and influence between the research variables. In conclusion, Competence has a partial effect on the quality of the financial statements of the Directorate of Drug Investigation of the South Sumatra Regional Police. Organizational behavior does not have a partial effect on the quality of the financial statements of the Directorate of Narcotics Police Investigation in South Sumatra. Competency, Organizational Behavior and Commitment simultaneously influence the Financial Report Quality of the South Sumatra Police Narcotics Investigation Directorate